The Determinants of Perception of Corruption in Guatemala, 2006–2016. (2nd September 2020) - Navia, Patricio; Perelló, Lucas; Masek, Vaclav
Abstract : The September 2015 ousting and imprisonment of Guatemalan President Otto Pérez Molina and the subsequent election of television personality Jimmy Morales, who ran on an anticorruption platform, were interpreted as evidence of the salience of corruption as a popular concern in the country. Using the Latin American Public Opinion Project (LAPOP) from 2006 to 2016, this article analyzes the evolution in the perception of corruption in Guatemala and its determinants to assess for changes after 2015. Perception of corruption remains a secondary concern for most Guatemalans and its determinants—age; education; rightwing ideology; and retrospective economic outlook—are stable overtime. The 2015 corruption scandal had a marginal impact on an already high perception of corruption. When perception of corruption is so widespread, the explanatory power of its determinants becomes less pronounced.